Cost and utilization analysis of concurrent versus staged testicular prosthesis implantation for radical orchiectomy - Nguyen, Vi; Walia, Arman; Horns, Joshua J.; Paudel, Niraj; Bagrodia, Aditya; Patel, Darshan P.; Hsieh, Tung-Chin; Hotaling, James M. (PLOS ONE, 2024)
Purpose American Urological Association guidelines recommend testicular prosthesis discussion prior to orchiectomy. Utilization may be low. We compared outcomes and care utilization between concurrent implant (CI) and staged implant (SI) insertion after radical orchiectomy. Materials & methods The MarketScan Commercial claims database (2008–2017) was queried for men ages >18 years who underwent radical orchiectomy for testicular mass, stratified as orchiectomy with no implant, CI, or SI. 90-day outcomes included rate of reoperation, readmission, emergency department (ED) presentation, and outpatient visits. Regression models provided rate ratio comparison. Results 8803 patients (8564 no implant, 190 CI, 49 SI; 2.7% implant rate) were identified with no difference in age, Charlson Comorbidity Index, insurance plan, additional cancer treatment, or metastasis. Median perioperative cost at orchiectomy (+/- implant) for no implant, CI, and SI were 5682 (3648–8554), 7823 (5403–10973), and 5380 (4130–10521), respectively (p<0.001). Median perioperative cost for SI at implantation was 8180 (4920–14591) for a total cost (orchiectomy + implant) of 13650 (5380 + 8180). CI patients were more likely to have follow-up (p = 0.006) with more visits (p = 0.030) compared to the SI group post-implantation but had similar follow-up (p = 0.065) and less visits (p = 0.025) compared to the SI patients’ post-orchiectomy period. Overall explant rates were 4.7% for CI and 14.3% for SI (p = 0.04) with a median time to explant of 166 (IQR: 135–210) and 40 days (IQR: 9.5–141.5; p = 0.06). Median cost of removal was 2060 (IQR: 967–2880). Conclusions CI placement has less total perioperative cost, lower explant rate, and similar postoperative utilization to SI.